The Effectiveness of Zhu Scalp Acupuncture and Body Acupuncture Therapy Methods on Increasing Intellectual Quotients and Emotional Quotients in Pre-School Children - Christiyawati, Maria; Estuningsih, Estuningsih (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Intellectual Quotients (IQ) is the ability to act purposefully, think rationally, and deal effectively with the environment. Emotional Quotients (EQ) includes empathy, expressing and understanding, feeling, controlling anger, independence, adaptability, liking, interpersonal problem-solving ability, perseverance, solidarity, friendliness, and respect; important for a person’s success. Acupuncture therapy with Zhu Scalp and body acupuncture methods can be used to increase IQ and EQ in children. AIM: This study was to determine the effectiveness of acupuncture therapy with Zhu Scalp acupuncture and body acupuncture methods on the IQ and EQ of pre-school children. METHODS: The research method is a quantitative pre and post-test design with cross-sectional control with a paired T-test. The research sample was pre-school children in Sukoharjo district with a total of 54 respondents. The data collection instrument is a questionnaire for respondent characteristics, IQ test, and EQ measurement using VSMS (Vineland Social Maturity Scale). RESULTS: The research results showed chitosan 5%; a combination of chitosan 9% and snail seromucous 50% (ratio 1: 1) is a microbicide against MTB TB patient isolates. Snail seromucous was ineffective as a microbicide against MTB tuberculosis patients. The results showed that there was a significant difference in the IQ and EQ levels of children before and after acupuncture therapy using the Zhu Scalp method and body acupuncture with a p-value of 0.000. The results of the N Gain test showed that there are differences in the effectiveness of the Zhu Scalp acupuncture and the body acupuncture method on increasing IQ and EQ in pre-school children. CONCLUSION: The Zhu Scalp acupuncture method is more effective than the body acupuncture method to increase IQ and EQ of pre-school age children, which can be applied in the management of acupuncture therapy to improve child development.